2022
DOI: 10.17507/tpls.1203.03
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting EMI Attitudes of Engineering and Nursing Students

Abstract: The internationalization of higher education has led to the increasing number of English as a Medium of Instruction (EMI) programs in contexts where English is not the first language nor the medium of communication, including Thailand. The introduction of EMI programs, however, is not without challenges. Therefore, a survey questionnaire was used to investigate the attitudes of engineering and nursing students toward EMI. Differences of attitudes based on the program of study, gender, nationality, year level, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 16 publications
3
10
0
Order By: Relevance
“…Unlike language classes where interactions are encouraged, EMI courses may have to focus on delivering content with a minimal language component. As found in EMI literature, content teachers hardly integrate language into their teaching due to a lack of linguistic competence or time constraints [36]. Further investigation of this issue using CLIL [32] would enhance our understanding of how lack of autonomy happens or at least how autonomy can be promoted in EMI programs, courses or lessons.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Unlike language classes where interactions are encouraged, EMI courses may have to focus on delivering content with a minimal language component. As found in EMI literature, content teachers hardly integrate language into their teaching due to a lack of linguistic competence or time constraints [36]. Further investigation of this issue using CLIL [32] would enhance our understanding of how lack of autonomy happens or at least how autonomy can be promoted in EMI programs, courses or lessons.…”
Section: Discussionmentioning
confidence: 99%
“…In Thailand, studies have focused on perceptions of teachers towards content and language instruction in EMI [32], teacher beliefs and practices [33,34], and attitude of students towards EMI [35,36].…”
Section: English Medium Instructionmentioning
confidence: 99%
See 1 more Smart Citation
“…4.3 Curriculum design and implementation challenges: Roshini et al ( 38 ), Khan ( 36 ), and Wilang and Nupong ( 60 ) discuss the complexities of curriculum design in the context of EMI. Roshini et al ( 38 ) observed that dental students faced educational challenges when English was not the primary language of instruction, pointing to the need for curricula that accommodate diverse language backgrounds.…”
Section: Main Findingsmentioning
confidence: 99%
“…Many researchers have studied the impact of EMI on higher education in non-English-speaking countries. In the Thai context, for example, the study by Wilang and Nupong (2022) found that the benefits of EMI include improving students' English proficiency and making higher education more competitive to meet growing local, national, and international requirements. In a similar line, Phuong and Nguyen (2019) also found that EMI provides four clusters of benefits.…”
Section: Literature Reviewmentioning
confidence: 99%